The relationship between executive functions and fluid intelligence in multiple sclerosis - Goitia, Belén (2020)
Background & objective Deficits in cognitive functions dependent upon the integrity of the prefrontal cortex have been described in Multiple Sclerosis (MS). In a series of studies we have shown that fluid intelligence (g) is a substantial contributor to frontal deficits and that, for some classical “executive” tasks, frontal deficits were entirely explained by g. However, for another group of frontal tasks deficits remained once g was introduced as a covariate. This second set of tests included multitasking and theory of mind tasks. In the present study, we aimed at determining the role of fluid intelligence in frontal deficits seen in patients with MS. Methods A group of patients with Relapsing Remitting MS (n = 36) and a group of control subjects (n = 42) were assessed with a battery of classical executive tests (which included the Wisconsin Card Sorting Test, Verbal Fluency, and Trail Making Test B), a multitasking test, a theory of mind test and a fluid intelligence test. Results MS patients showed significant deficits in the fluid intelligence task. We found differences between patients and control subjects in all tests except for the multitasking test. The differences in the classical executive tests became non-significant once fluid intelligence was introduced as a covariate, but differences in theory of mind remained. Conclusions The present results suggest that fluid intelligence can be affected in MS and that this impairment can play a role in the executive deficits described in MS.